ENTREPRENEURIAL CHARACTERISTICS AMONGST UNIVERSITY STUDENTS IN ALBANIA - Anisa Kume; Vasilika Kume; Besa Shahini (European Scientific Journal, ESJ, 2013)
Entrepreneurship education is an important solution to the employment difficulty of university graduates by guiding them to organize a new business venture. Some questions are frequently posed:What are the factors that inspire entrepreneurialism in college students in Albania? What kinds of students are most likely to become entrepreneurs? Are male students more inclined toward entrepreneurialism than are female students?This study investigates the tendency towards entrepreneurship among university students in Albania. Specifically, it aims to examine the relationship between the desire for having your own business and family business background on university students.The survey centered around two dimensions: entrepreneurial attitude, defined as the degree of positivity one feels towards the idea of becoming an entrepreneur; and motivation factors for growing their own business. To define the entrepreneurial profile of students four traits are used: locus of control, entrepreneurial self-efficacy, independence motive, innovation motive.The question “What are your career expectations for the time directly after your studies?” was asked to students in order to do a distinction between those who are entrepreneurially disposed and those who are not. Those who responded “I'm going to start-up my own business” are considered as potential entrepreneurs. Then, the entrepreneurial traits of these students are compared with other students who do not plan to start their own businesses.The study is conducted on a random sample of fourth year university students (n= 519) from three Albanian universities.This paper argues that it is very necessary for Albanian universities to introduce sustainable development ideas to their entrepreneurship education and re-orientate the education objectives, content and methodology of entrepreneurship education.